If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7k + 6 = 69 Reorder the terms: 6 + 7k = 69 Solving 6 + 7k = 69 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 7k = 69 + -6 Combine like terms: 6 + -6 = 0 0 + 7k = 69 + -6 7k = 69 + -6 Combine like terms: 69 + -6 = 63 7k = 63 Divide each side by '7'. k = 9 Simplifying k = 9
| 4-7(3x-1)=-4x+28 | | 127=(16*59.3/x)(16*9.9/x) | | p-8=-15/p | | -6x+7+7x=9 | | x-sqrt(11-10x)=-22 | | 10xwhat=990 | | 4x+6=4+3x | | 5t-9=31 | | 7k-5=30 | | 6a-5=43 | | -30-6a=2(1-7a) | | 7a^2-24a-4=0 | | 31+6n=-5(1-3n) | | 4(2)-3/2(1)-1 | | 2x+26=0 | | -9+2x+4x=9 | | 5x-6x-3=-5 | | 6+4(3-2n)=-4n+14 | | 1/6=1.5x | | 8y=-3x+4 | | 5b-2=18 | | 52x^3-122x^2+66x=0 | | -2n=6-2n | | -8x+8+5x=2 | | -3x+3=2 | | 6x+4.50y=45 | | 20.4/3.4= | | 2x/9-9/3=8-3x | | 6(x-2)+5x=9x-2(4-3) | | 9x+4=64 | | -7x+2y=70 | | .66x-6+3=4x-4 |